Religious and political conservatism and beliefs about same-sex parenting in Portugal - Costa, Pedro Alexandre (2014)
Aim: During the last decade, there have been political changes regarding the rights of Lesbian, Gay, Bisexual, and Transgender (LGBT) individuals in Portugal, such as the right to marry. However, parenting by same-sex couples is not legally allowed. The purpose of this study was to assess Portuguese heterosexuals’ beliefs about same-sex parenting, and the role of religious and political conservatism in shaping these beliefs. Method: A total of 993 participants, aged between 18 and 69 years (M = 34; SD = 11), responded to one of three questionnaires that included a case vignette depicting a different-sex, a female same-sex, or a male same-sex couple wishing to adopt a child. Participants were then asked to evaluate whether the couple would be suitable to adopt a child, and whether they anticipated any social and emotional problems with the child. Results: Participants consistently anticipated more children’s social and emotional problems if they were adopted by a same-sex couple. Men evaluated same-sex couples less favourably than women, and even less so the male same-sex couple. Conclusion: It was found that both religious conservatism and right-wing political leaning were associated with more sexual prejudicial beliefs regarding same-sex couples.